Evaluating a specialized autism spectrum disorder clinic in Qatar: A multidisciplinary model for comprehensive assessment and diagnosis - Yasser Saeed Khan (17191735) (2025)
An accurate diagnosis of autism spectrum disorder (ASD) can be complex due to the high degree of phenotypical variation and the necessity to integrate information from multiple assessments by various professionals. This paper examines the implementation and effectiveness of a specialized Autism ASD Assessment Clinic within the Child and Adolescent Mental Health Service (CAMHS). The clinic addresses a critical service gap in the Middle East and North Africa (MENA) region by offering structured, comprehensive evaluations for ASD using a multidisciplinary team (MDT) model, aiming to provide comprehensive and standardized assessments for children and adolescents aged 6–17 years suspected of having ASD. The methodology involved obtaining feedback from parents/caregivers through a Likert-scale questionnaire following the completion of the assessment for children and adolescents referred to the clinic between January 2022 and December 2024. Out of 48 families who attended the appointments and completed the assessment, 27 parents/caregivers completed the feedback. High satisfaction rates with the assessment's thoroughness, professionalism of the MDT, and clarity of feedback were observed. A statistically significant inverse correlation was found between a child's age and parental satisfaction with assessment thoroughness and clarity of feedback, suggesting higher satisfaction among parents of younger children. The findings highlight the clinic's effectiveness in delivering quality care, improving early support for diagnosed individuals, and providing enhanced experience to families. Other Information Published in: Research in Developmental Disabilities License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ridd.2025.105109